The role of mindfulness in savoring beliefs and positive & negative affect - Johnson, Katelyn (My University, 2009)
In the present study we investigated self-reported levels of mindfulness and its relation to both emotion regulation and mood. It was hypothesized that higher levels of mindfulness would be associated with reports of more adaptive emotion regulation strategies. Higher levels of mindfulness were also anticipated to relate to a neutral level of mood. In addition, it was hypothesized that a greater difficulty in regulating emotions would be related to higher negative affect and lower positive affect. Our results showed that a greater ability to be in the moment was related to a greater ability to regulate emotions. We also found that greater difficulty in regulating emotions was related to higher levels of negative mood and lower levels of positive mood. However, we did not find the expected neutral relationship between mindfulness level and mood. Instead, we found that mindfulness is related to higher levels of positive affect and lower levels of negative affect. Further analyses showed that emotion regulation might be mediating the relationship found between the mindfulness ability to be nonjudging in the moment and mood. This study extends the literature on mindfulness and mood to also include the possible mediating role of emotion regulation, which may be important in helping us to understand how the ability to be nonjudging of the moment might allow individuals to be accept emotional experiences that occur.
Date original was created: 2009 This file was last viewed in Adobe Acrobat 9.0
Keywords: Attention; Emotions; Thought and thinking; Consciousness; Awareness